Effects of branch dimensions of fodder trees on their utilization by ruminants - Santana-Pérez, Ángel Arturo; Borrás-Sandoval, Luis Miguel; Cheng, Long; Verdecia-Acosta, Danis Manuel; Iglesias-Gómez, Jesús Manuel; Vega-Albi, Ana Mercedes; Ramírez-de-la-Ribera, Jorge Luis (Universidad Pedagógica y Tecnológica de Colombia, 2019)
To determine the stem measurements (length and diameter) up to which forage trees (Leucaena leucocephala, LL; Albizia lebbeck, AL; Gliricidia sepium, GS; Moringa oleifera, MO; Samanea saman, SS) are consumed by cattle and sheep (young or adult), these foliages were daily offered to the animals and the minimal diameters of the refused branches were measured (maximal diameter of the eaten fragment). More than 300 dimensions of stem length vs. its corresponding diameter were paired. It was done a triple analysis of variance (5x2x2) being the factors: forage species, animal species and animal age. A simple regression analysis was done between length and diameter of the stalks, as well as a probability test of Z to consider 5% refuse of the foliage by the animals. The results showed that the diameters of the eaten stems are different for each foliage species, being GS>LL>MO>SS>AL, this means that each one has to be cut at a different dimension, this cut must be different for cattle and sheep, but not between ages of them and that sheep do not consume any stem of SS and GS. Finally, it is recommended the exact dimensions of the stems (diameter and length) to cut each species and the evaluation methodology to be used for other fodder evaluations.